The Tragedy of Othello - Shakespeare, William (New York Pocket Books, 1957)
Othello, a noble black Moor, has spent his life as a soldier and become a general in the army of Venice. He marries Desdemona, a beautiful Venetian girl much younger than himself. Almost immeadiately after the marriage, Othello is ordered to Cyprus, where Desdemona joins him. Othellos villainous aide, Iago, hates the Moor. Iago decides to destroy Othello by persuading him that Desdemona has made love with Cassio, Othellos lieutenant...
Keywords: Literature